Identification of Nuclear Effects in Neutrino-Carbon Interactions at Low Three-Momentum Transfer - Rodrigues, PA (2016)
We are grateful to the authors of the RPA and 2p2h models for making the code for their calculations available for study and incorporation into this analysis. This work was supported by the Fermi National Accelerator Laboratory under U.S. Department of Energy Contract No. DE-AC02-07CH11359, which included the MINERvA construction project. Construction support was also granted by the United States National Science Foundation under Grant No. PHY-0619727 and by the University of Rochester. Support for scientists for this specific publication was granted by the United States National Science Foundation under Grant No. PHY-1306944. Support for participating scientists was provided by NSF and DOE (USA) by CAPES and CNPq (Brazil), by CoNaCyT (Mexico), by CONICYT (Chile), by CONCYTEC, DGI-PUCP and IDI/IGI-UNI (Peru), and by Latin American Center for Physics (CLAF). We thank the MINOS Collaboration for use of its near detector data. Finally, we thank the staff of Fermilab for support of the beam line, the detector, and the computing infrastructure.